Does Gamified Educational Systems Change Students’ Learning Behaviors? A Case Study with Postgraduate Students - Oliveira dos Santos, Wilk; Toda, Armando; Isotani, Seiji; Ibert Bittencourt, Ig (RENOTE, 2018)
In the last few years, gamification studies have increased in the field of education and digital technologies, showing different results on the use of gamified educational systems in relation to students’ learning aspects. These studies, however, often keep the focus on quantitative or qualitative approaches directly related to student learning, without considering students’ perceptions of the gamification design and how the gamification design aspects of the system can influence positively the students’ behavior change. Therefore, this study compared a gamified with a non-gamified version of an educational system, through a mixed (quantitative and qualitative) approach to identify if gamified educational systems are better than non-gamified educational systems to provide positive students’ learning behavior change. The results confirmed that the gamified educational system was more effective than the non-gamified system.